The modulation of PD-L1 induced by the oncogenic HBXIP for breast cancer growth - Xu Fei-fei; Sun Hui-min; Fang Run-ping; Zhang Lu; Shi Hui; Wang Xue; Fu Xue-li; Li Xian-meng; Shi Xu-he; Wu Yue; Ye Kai; Zhang Wei-ying; et al. (Acta Pharmacologica Sinica, 2022)
Programmed death ligand-1 (PD-L1)/PD-1 checkpoint extensively serves as a central mediator of immunosuppression. A tumor- promoting role for abundant PD-L1 in several cancers is revealed. However, the importance of PD-L1 and how the PD-L1 expression is controlled in breast cancer remains obscure. Here, the mechanisms of controlling PD-L1 at the transcription and protein acetylation levels in promoting breast cancer growth are presented. Overexpressed PD-L1 accelerates breast cancer growth in vitro and in vivo. RNA-seq uncovers that PD-L1 can induce some target genes affecting many cellular processes, especially cancer development. In clinical breast cancer tissues and cells, PD-L1 and HBXIP are both increased, and their expressions are positively correlated. Mechanistic exploration identifies that HBXIP stimulates the transcription of PD-L1 through co-activating ETS2. Specifically, HBXIP induces PD-L1 acetylation at K270 site through interacting with acetyltransferase p300, leading to the stability of PD-L1 protein. Functionally, depletion of HBXIP attenuates PD-L1-accelerated breast tumor growth. Aspirin alleviates breast cancer via targeting PD-L1 and HBXIP. Collectively, the findings display new light into the mechanisms of controlling tumor PD-L1 and broaden the utility for PD-L1 as a target in breast cancer therapy.